Analisis Manajemen Pengembangan Bahan Ajar Berupa Alat Peraga dalam Mendukung Kualitas Pembelajaran di TPQ Miftahur Rohmah - Toni Choirul Sidik; Muhammad Syafi’i (Indo Publishing, 2026)
This study aims to analyze the management of teaching material development in the form of instructional aids to support the quality of learning at TPQ Miftahur Rohmah. This research uses a qualitative approach with a field study design. Data were collected through in-depth interviews, observation, and documentation involving the head of TPQ, teachers (ustadz/ustadzah), and students. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, consisting of data reduction, data display, and conclusion drawing. The findings show that the development of instructional materials in the form of teaching aids (levels 1–6, ghorib, and tajwid) is carried out in a simple and needs-based manner. Planning is based on students’ initial ability tests, organizing involves the head of TPQ and teachers, implementation is carried out through direct use of teaching aids in classroom learning, and evaluation is conducted through observation of students’ Qur’an reading progress and internal discussions. The use of teaching aids improves students’ understanding, increases learning interaction, and enhances student engagement. The study concludes that the management of teaching material development based on instructional aids in TPQ is flexible, collaborative, and contextual to the needs of non-formal education